2004
DOI: 10.1209/epl/i2003-10305-x
|View full text |Cite
|
Sign up to set email alerts
|

Spin Josephson effect in ferromagnet/ferromagnet tunnel junctions

Abstract: PACS. 72.25.-b -Spin polarized transport. PACS. 72.25.Mk -Spin transport through interfaces. PACS. 74.50.+r -Tunneling phenomena; point contacts, weak links, Josephson effects.Abstract. -We consider the tunnel current between two ferromagnetic metals from a perspective similar to the one used in superconductor/superconductor tunnel junctions. We use fundamental arguments to derive a Josephson-like tunnel spin current I spin J ∝ sin(θ1 − θ2).Here the phases are associated with the planar contribution to the mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
108
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(118 citation statements)
references
References 33 publications
9
108
1
Order By: Relevance
“…[21][22][23] The spin quantum axis is taken as the magnetic moment direction of the left FM lead h L (0,0,1) and the magnetic moment in the right FM lead is same as that in the last subsection h R (sin θ cos φ, sin θ sin φ, cos θ). Using the Green's function (Eq.…”
Section: Fm/fmmentioning
confidence: 99%
See 2 more Smart Citations
“…[21][22][23] The spin quantum axis is taken as the magnetic moment direction of the left FM lead h L (0,0,1) and the magnetic moment in the right FM lead is same as that in the last subsection h R (sin θ cos φ, sin θ sin φ, cos θ). Using the Green's function (Eq.…”
Section: Fm/fmmentioning
confidence: 99%
“…For the FM/FM tunnelling junction, a spontaneous ESC has been verified [20][21][22][23] flowing across the interface when the two magnetic moments h l and h r in the two leads of the junction are not collinear, and their exchange interaction determines the ESC J s , J s ∼ h l × h r . This indicates non-collinear magnetizations in the two leads can lead to spin flip and consequently a ESC through the junction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2(c), µ z R is plotted as a function of system length, L. For small system sizes, µ z R is independent of L, as in the SSF Eqs. (1) and (2). For intermediate film sizes, the dynamic dipole field dominates the exchange interaction.…”
mentioning
confidence: 99%
“…It has been suggested that certain ferromagnets may exhibit spin superfluidity (SSF) [1][2][3]. The superfluid spin-drag properties induced by spin transfer and spin pumping (SP) in a normal metal-ferromagnetnormal metal system have recently been computed [4][5][6].…”
mentioning
confidence: 99%